-(41p-82q+80)=

Simple and best practice solution for -(41p-82q+80)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(41p-82q+80)= equation:


Simplifying
-1(41p + -82q + 80) = 0

Reorder the terms:
-1(80 + 41p + -82q) = 0
(80 * -1 + 41p * -1 + -82q * -1) = 0
(-80 + -41p + 82q) = 0

Solving
-80 + -41p + 82q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '80' to each side of the equation.
-80 + -41p + 80 + 82q = 0 + 80

Reorder the terms:
-80 + 80 + -41p + 82q = 0 + 80

Combine like terms: -80 + 80 = 0
0 + -41p + 82q = 0 + 80
-41p + 82q = 0 + 80

Combine like terms: 0 + 80 = 80
-41p + 82q = 80

Add '-82q' to each side of the equation.
-41p + 82q + -82q = 80 + -82q

Combine like terms: 82q + -82q = 0
-41p + 0 = 80 + -82q
-41p = 80 + -82q

Divide each side by '-41'.
p = -1.951219512 + 2q

Simplifying
p = -1.951219512 + 2q

See similar equations:

| -42=2(7n+7) | | 2(5t-3)=3(2t+6) | | 5(2x-z)=7h | | x^3+2x^2-8x-16=0 | | 5(x-5)=x(14-4) | | 5(2x-4)=2(3x+2) | | -7(p+7)=-21 | | 38+x=2(11+x) | | 4(3x-5)=2(x-5) | | 6(m+3)=2(m-1) | | -1-x^2=0 | | 56=-8(1+n) | | 0=4+2x-2x | | 2(4x+3)=3(2x+4) | | -(v+6)=-14 | | x^2+36x=0 | | 3(2x-3)=5(x+1) | | 8(x+9)=8x+72 | | 3x-2y-4=7y+6 | | 3x-5=x^2 | | (x+4)(2x+1)=(2x+5)(2-x) | | 27x+9=3x+30+3x | | A=1/2*70(40+160) | | 13m+3n-6m+9n= | | -4x^2-12x-3=0 | | (x+0.6)(x+1.6)=0 | | y=-16x^2 | | (2x-3)*(x+5)+7=(x-4)*(2x-1)+20 | | 7x^3+y^3+3xy(x-y)-12x^2+6x=1 | | 4x-(x+3)=(2x+5) | | (2x-3)*(x+5)+7=(x-4)*(2x-1)+2 | | x/2+x/3+200=x |

Equations solver categories